INJURIES AND ILLNESS DURING MASS-PARTICIPATION TRIATHLON RACES: OPTIMISING COMPETITOR SAFETY. Issue 4 (1st February 2017) - Kipps, Courtney; Smith, Ralph; Knight, Nick; Parkin, James
Abstract : Background: Triathlon is an increasingly popular mass-participation endurance sport which incorporates swimming, cycling and running stages over a variety of distances. Overuse injuries during triathlon training are common (Zwingenberger et al . 2014; Korkia et al . 1994) however the incidence of illness and injury during triathlon races is less well described. A clear understanding of this data is valuable in planning medical care for mass-participation triathlon races. Objective: To describe the epidemiology of illness and injuries during triathlon races in the UK. Design: Retrospective analysis of competitors' medical records (CMRs). Setting: Two large summer triathlons over 5 years. Participants: All triathlon competitors requiring treatment by the triathlon medical team (TMT) for illness or injury (excluding first aid). Assessment of Risk Factors: Age, gender, race distance, race experience, mechanism of injury, co-morbidities, and medical management was recorded. Main Outcome Measurements: Number of cases of medical illness, musculoskeletal (MSK) injury, and topical injury (e.g. abrasions) treated by the TMT. Results: There were 68557 starters and 67270 finishers across Supersprint, Sprint, Olympic and OlympicPlus distances (2.3% did not finish) from 11 consecutive events. The TMT treated 429 competitors (0.62%, 1/161 starters) for complaints including falls, fractures, breathlessness and collapse. Medical illness was the most common complaint (44.1%), followed by MSK injury (27.1%) and topical injury (24.8%). There were three cardiorespiratory arrests during the swim leg including two successful resuscitations (1/34279 starters) and one fatality (1/68557). The run leg was responsible for most MSK injuries (41.4% of all injuries) and nearly a third (11/38) of all hospital transfers. Conclusions: Triathlons have a high incidence of both illness and injury. The swim leg had the most serious medical conditions whilst the run accounted for most injuries. Triathlon organisers should be aware of these findings to ensure optimal medical care and competitor safety at mass-participation triathlon races.